Newtons Methodologie: Eine Kritik an Duhem, Feyerabend und Lakatos. - Feldbacher-Escamilla, Christian J. (Archiv für Geschichte der Philosophie, 2019)
The Newtonian research program consists of the core axioms of the Principia Mathematica, a sequence of force laws and auxiliary hypotheses, and a set of methodological rules. The latter underwent several changes and so it is sometimes claimed that, historically seen, Newton and the Newtonians added methodological rules post constructione in order to further support their research agenda. An argument of Duhem, Feyerabend, and Lakatos aims to provide a theoretical reason why Newton could not have come up with his theory of the Principia in accordance with his own methodology: Since Newton's starting point, Kepler's laws, contradict the law of universal gravitation, he could not have applied the so-called method of analysis and synthesis. In this paper, this argument is examined with reference to the Principia's several editions. Newton's method is characterized, and necessary general background assumptions of the argument are made explicit. Finally, the argument is criticized based on a contemporary philosophy of science point of view.